Deep beyond (2021), volume 2 ebook - Andolfo, Mirka (Deep Beyond (2021), 2022)
In an underpopulated future Earth, devastated by the dire consequences of the millennium bug, the survival of mankind—and, maybe, of the planet itself—is handled by a small number of people. These are talented scientists who, despite the adverse situation and the stupid feuds that continue to divide the small number of people still alive, try to understand and study what is hidden in the depths of the abyss—something mysterious and dangerous, which could eventually cause an even worse and more destructive catastrophe!